Mitochondrial Extracellular Vesicles in CNS Disorders: New Frontiers in Understanding the Neurological Disorders of the Brain - Nakamya, Mary F.; Sil, Susmita; Buch, Shilpa; Hakami, Ramin M. (Frontiers in Molecular Biosciences, 2022)
Recent findings have highlighted potential diagnostic and prognostic values of extracellular vesicles (EVs) that contain mitochondrial derived components for neurological disorders. Furthermore, functional influences of vesicles carrying mitochondrial components have been reported. In particular, this includes indications of crosstalk with mitophagy to influence progression of various CNS disorders. In this mini-review, we discuss the current state of knowledge about this intriguing class of vesicles in neurological disorders of the CNS, and outline the lacunae and thus scope of further development in this fascinating field of study.